Baby boomers and their growing interest in spa and wellness tourism. Issue 3 (2nd September 2022) - Patterson, Ian; Balderas-Cejudo, Adela
ABSTRACT: Wellness tourism services are usually provided in hotels and health resorts with day spas that use natural therapy packages consisting of different fitness and beauty treatments. This paper will focus on the growing importance of wellness tourism to baby boomers (who were born between 1946 and 1964), because these types of services are beneficial from a medical, wellness and social perspective. Many older travellers are seeking out alternative forms of treatment at spa resorts in an attempt to help them fulfil their desire for "youthfulness, " and as a means of providing physical and spiritual balance for their bodies. For others, it may depend on the types of treatments and natural remedies which are specifically available at European destination spa resorts to help treat specific types of chronic diseases and illnesses. Social tourism also has a positive impact on older people's subjective wellbeing, and their level of social engagement has helped to increase self-esteem and confidence levels. Emotional and psychological wellbeing were found to be vital for "ageing well" and for baby boomers in particular, wellness tourism provides opportunities for increased social interaction and companionship that have a positive impact on their wellbeing.